Hubungan Kualitas Pelayanan Kefarmasian Terhadap Kepuasan Pasien Rawat Jalan RS Bhayangkara TK. III Banjarmasin - Maulina Lisdawati; Nily Su’aida; Aris Fadillah (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2026)
Background: The quality of pharmaceutical services is a crucial factor in the success of treatment and patient satisfaction. Objective: This study aims to analyze the relationship between the quality of pharmaceutical services and the satisfaction of outpatients at RS Bhayangkara TK. III Banjarmasin. Methods: This study employs a descriptive quantitative method with a survey approach, where data is collected through questionnaires distributed to patients receiving services at the hospital’s pharmacy department. Results: The results indicate a significant relationship between the quality of pharmaceutical services and patient satisfaction (p–value = 0,000 ≤ 0,05) analyzed through five dimensions of service quality: tangibility, reliability, responsiveness, assurance, and empathy. The Chi-Square test analysis showed that all these dimensions positively contribute to patient satisfaction. Additionally, this study evaluated the waiting time for both compounded and non-compounded medications, revealing that the hospital’s pharmacy services comply with the time standards set by the Ministry of Health. Conclusions: This study confirms the significant relationship between the quality of pharmaceutical services and outpatient satisfaction at Bhayangkara level III Hospital. Higher service quality, greater outpatient satisfaction, highlighting the need for continuous improvement in pharmaceutical services.